Study the Reproductive Pattern of Different Breeds Bitches in Iraq by estimation of Kisspeptin and detection ovulation time. - Sulake Fadhil Abbas Al-Zubaidi; Souhayla O. Hussain (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study was conducted to investigate the reproductive pattern of bitches by estimation the optimumtime of ovulation and kisspeptin level. The study included 245 bitches (different breeds), from March/2019to the end of February/2020.Canine ovulation timing kits was applied in order to determine the ovulationtime. For estimation of Kisspeptin, blood collection of 80 samples allocated approximately 7 samples foreach monthby using ELISA kit. The resultsrevealed the time of ovulation ranged from 2 to 5 days after thebeginning of the estrus phase.The results showed that concentration of kisspeptin during different phases ofthe estrous cycle was (257.01±11.08, 262.93±9.15, 227.98±14.91 and 244.89±11.99) pg/mL for Proestrus,Estrus, Diestrus, and Anestrus respectively with no significant (p>0.05) differences among different estrouscycle phase. The concentration of kisspeptin in which distributed according to the season showed that itwas (218.26±11.92, 254.12±10.09, 246.00±10.22, and 287.11±9.00) pg/ml for Spring, Summer, Autumn,and Winter, respectively and there was a significant difference (p<0.05) between Summer and Winter. Asa conclusion, the ovulation timing kit was accurate and useful for detecting the time of ovulation and theseason had a significant effect on the kisspeptin level.